The economist's craft an introduction to research, publishing, and professional development - Weisbach, Michael S. (Michael Steven) (Skills for scholars (Princeton University Press), 2021)
"The Economist's Craft introduces graduate students and rising scholars to the essentials of research, writing, and other critical skills for a successful career in economics. Michael Weisbach enables you to become more effective at communicating your ideas, emphasizing the importance of choosing topics that will have a lasting impact. He explains how to write clearly and compellingly, present and publish your findings, navigate the job market, and more. Walking readers through each stage of a research project, Weisbach demonstrates how to develop research around a theme so that the value from a body of work is more than the sum of its individual papers. He discusses how to structure each section of an academic article and describes the steps that follow the completion of an initial draft, from presenting and revising to circulating and eventually publishing. Weisbach reveals how to get the most out of graduate school, how the journal review process works, how universities decide promotions and tenure, and how to manage your career and continue to seek out rewarding new opportunities. A how-to guide for the aspiring economist, The Economist's Craft covers a host of important issues rarely taught in the graduate classroom, providing readers with the tools and insights they need to succeed as professional scholars"--